Analisis Resiliensi Industri Property Dan Real Estate Di Tengah Masa Pemulihan Ekonomi Pandemi Covid-19 - Sholikhatin, Siti; Tojibusabirin, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to determine the level of resilience of industrial companies in the property and real estate sector which are listed on the Indonesia Stock Exchange in facing the recovery period due to the economic crisis in terms of profitability, liquidity, and solvency. The data collection method used by researchers is documentation obtained from the Indonesian Stock Exchange website and the websites of each company. The sample collection technique used was purposive sampling with 45 samples which are 9 companies and 5 for the 2017-2021 period. The researcher uses the Modified Altman Z-Score analysis model with the criteria for the Z